Vozes do desterro: a Literatura de Exílio alemã em seus periódicos e na obra de Anna Seghers - Andrade, Patrícia Helena Baialuna de [UNESP] (2015)
During the 1930's and the 1940's, as national-socialism raised its domain and made profound changes in German society - especially about liberty -, Germany's boundaries were crossed by an enormous number of intellectuals, oppositional politicians, artists and Jews. This massive emigration had as a result the establishment of groups of exiled people in several countries. Compelled to leave their country to escape persecution and even risk to their own lives, these men and women faced all sorts of difficulties related to exile; nevertheless, many of them used every possible resource to engage themselves into an opposition movement against fascism, which was formed among the intellectuals and tried to reach a wider circle through publications. Starting with some reflections about exile and its representations in some classic universal literature pieces, we focus on the specific German case, aiming to better understand the historical - political, social and cultural - conditions that caused the diaspora of the most important names of German arts. The literature produced by the Germans living in foreign countries, named Exilliteratur, is the object of this study through one of its most relevant manifestations: the periodicals, magazines about literature and politics, on whose pages some of the most important issues of that time have been discussed, aesthetical and ideological. We aim to expose the importance of these periodicals to the Exilliteratur in general and to the constitution of a movement against Nazism. Amongst the main names of this movement is Anna Seghers', a Jew and communist writer forced to exile. Novels and short stories written by Seghers during her exile years are the highest renowned of her vast bibliography. As we present some of these texts, we aim to point to the ways the engagement and problems of that historical moment are transformed into literary art pieces